E-procurement in Permodalan Nasional Berhad: benefits and challenges / Muhammad Khairul Hazwan Zainal - Zainal, Muhammad Khairul Hazwan (Faculty of Business and Management, 2009)
The procurement concept is moving ahead from traditional manual paper-based to electronically-based due to improvement in Internet and World Wide Web technology. In such a highly competitive environment nowadays, it is necessary for every company to maintain an efficient and effective procurement to cut administration cost and to keep abreast of the market condition to procure materials at the right price, quality and time. The main objective of this study is to identify factors or challenges that affecting implementation of E-procurement and benefits that come from the implementation of E-procurement. Research methodology includes comprehensive literature review and other method such as observation and interview. The findings of the research shows that four benefits of E-Procurement from PNB’s Experience that are monitoring requisition process, avoid Stigma on Procurement, key Performance Index (KPI) Management and better management and increase efficiency. Eight challenges of implementing e-Procurement in PNB has been determined that are purchasing not viewed as a strategic function, implementation cost, inappropriate cost consideration, trading with strangers, security and privacy Issues, Lack of sound Internet infrastructure and security, people and perception (E-readiness) and trust and reliability. Thus, PNB need to meet up with the current technology and find a solution for all challenges determined in the research.